Allele‐specific analysis of single parent backcross population identifies HOX10 transcription factor as a candidate gene regulating rice root growth. Issue 2 (20th November 2018) - Reddy, Sowmya H.; Kambalimath, Sumanth K.; Singhal, Rajesh K.; Chikkakariyappa, Manjunath K.; Muthurajan, Raveendran; Rajanna, Mavinahalli P.; Sreevathsa, Rohini; Sevanthi, Amitha M.; Mohapatra, Trilochan; Sarla, Neelamraju; Chinnusamy, Viswanathan; Krishnan, Gopala S.; et al.
Abstract : Understanding the molecular and physiological mechanisms of trait diversity is crucial for crop improvement to achieve drought adaptation. Root traits such as high biomass and/or deep rootedness are undoubtedly important drought adaptive traits. The major aim of this investigation was to functionally characterize a set of ethyl methane sulfonate‐induced rice mutants for root traits. We report the identification of a high‐root biomass mutant through a novel screening strategy for yield and Δ 13 C measurements. The high‐root mutant (392‐9‐1) thus identified, had a 66% higher root biomass compared to wild‐type (Nagina‐22). Better maintenance of leaf turgor and carbon assimilation rates resulted in lower drought susceptibility index in 392‐9‐1. Targeted resequencing revealed three non‐synonymous single nucleotide variations in 392‐9‐1 for the genes HOX10, CITRATE SYNTHASE and ZEAXANTHIN EPOXIDASE . Segregation pattern of phenotype and mutant alleles in a single parent backcross F2 population revealed a typical 3:1 segregation for each of the mutant alleles. The number of F2 progeny with root biomass equal to or greater than that of 392‐9‐1 represented approximately one‐third of the population indicating a major role played by HOX10 gene in regulating root growth in rice. Allele‐specific Sanger sequencing in contrasting F2 progenies confirmed the co‐segregation of HOX10 allele with the root biomass. The non‐synonymous mutations in the other two genes did not reveal any specific pattern of co‐segregation with root phenotype, indicating a strong role of HOX10, an upstream transcription factor, in regulating root biomass in rice.